HARGA DIRI DAN KUALITAS HIDUP PADA PASIEN DENGAN CHRONIC KIDNEY DISEASE YANG MENJALANI HEMODIALISIS - Archentari, Kurniasih Ayu; Gasela, Vista; Nuriyyatiningrum, Nadya Ariyani Hasanah; Iskandarsyah, Aulia (Faculty of Psychology, Diponegoro University, 2017)
Patients with a chronic kidney disease encounter medical as well as psychological problems. They have to adjust to the daily changes in life as consequences of the required treatment. The need to take medication regularly, hemodialysis treatment, and reduce mobility because of limitation of physical abilities may cause distress and often impact on their self-esteem. This study aimed to investigate the correlation of self-esteem to quality of life on patients with chronic kidney disease who undergo hemodialysis. The study population is patients who join â€œKomunitas Hidup Ginjal Mudaâ€, a community of young people with kidney disease in the social media (Facebook) which has 371 members. The incidental sampling technique was applied and resulted in 34 patients joined the study as study participants. The Rosenberg Self-Esteem Scale and the Kidney Disease Quality of Life Short Form (version 1.3) were used to collect data. The results of product moment correlation analysis showed that there was a positive and significant correlation between self-esteem and quality of life among chronic kidney disease patients who undergo hemodialysis (r = .417; p = .014).